Convergence and divergence in British housing space. Issue 7 (3rd July 2018) - Gray, David
ABSTRACT: The degree of convergence that exists among British house prices is an open question. Inferences vary with the method applied and periods considered. Using the rank of the cointegrating matrix among four decades of regional data, two contiguous groups of regions are revealed. These super-regions have some common members through which price changes are transmitted from south to north. With London found to be deviating from the South East, neither it nor the UK are likely to be indicative of the regional series of the south of England.